Reassessing the use of vasodilators in heart failure. (September 2012) - Cole, Robert T; Gheorghiade, Mihai; Georgiopoulou, Vasiliki V; Gupta, Divya; Marti, Catherine N; Kalogeropoulos, Andreas P; Butler, Javed
Heart failure is a growing epidemic that currently affects nearly 6 million people in the USA. Despite the well-documented hemodynamic abnormalities associated with the disease (e.g., elevated systemic vascular resistance), therapies that directly target these derangements have consistently failed to improve important clinical outcomes, unless they also act on the underlying pathophysiology of the disease (e.g., angiotensin-converting enzyme inhibitors). Numerous clinical trials of vasodilators in the treatment of heart failure have resulted in either neutral or negative outcomes suggesting that systemic vascular resistance may be an inappropriate target of therapy. The reasons for failure in these studies are manifold, including a poor understanding of vasodilator agents and their secondary effects, poorly designed studies that include a markedly heterogeneous patient population and a paucity of objective end points that may be used as targets of therapy, to name a few. Future studies of vasodilators will need to consider these issues in trial design.